Practice of Social Responsibility in Moroccan Companies « An Exploratory Study » - El Mousadik, Mouna; El Kandoussi, Fatima (European Scientific Journal, ESJ, 2017)
This paper discusses the concept of Corporate Social Responsibility in the Moroccan context. The main purpose of this study is to draw up an inventory current situation of the CSR in Moroccan small business companies, as such to help understand the commitment of this type of business in sustainable economic development. It has been proven, by the survey among forty small Casablanca business leaders representing different sectors of activity, that the managers integrate unknowingly in their management the concept of SR, and that when it comes to social practices a link certainly exist between the company and its stakeholders (costumers, providers…). The survey shows that more than half of the interviewed executives stipulate that either they heard or know about SR; this awareness towards the concept is an increasing function which depend on the size of company. As also Moroccan leaders are aware of the advantages in engaging social responsibility approach in their business; this finding suggests as well that social responsibility can be of direct economic value for the firm.